Equality in the secondary school : promoting good practice across the curriculum - Cole, Mike, 1946- (Continuum International Pub. Group, 2009)
Drawing on a wealth of knowledge from a varied list of contributors, this volume addresses the importance of going beyond equal opportunities. The contributors provide a compelling argument for promoting equality in secondary schools. Issues covered include: social class; 'race'; gender; sexual orientation; disability and special educational needs with reference to all subjects taught at secondary school level.